Teaching Code of Ethics through Interactive Videos to Enhance Learner’s Engagement, Interest, and Performance (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In the fast-paced era of educational digitization, the nature of learning styles has been changing drastically, over the time with novel learning practices. In this study, to enhance a self-paced and personalized student learning experience, an integrated approach was implemented, based on the latest system of HTML5-based interactive videos content (H5P). The proposed approach accommodated to student’s affective and cognitive learning needs. The underpinnings of theoretical foundations included Brame’s effective educational videos framework, and Gagne’s Instructional design model. An experimental design was carried out to test the effectiveness of interactive videos in teaching the university code of ethics, which would result in better knowledge retention. Students were randomly selected from different universities (N=200). The participants were taught the university’s code of ethics, policies, and procedures using the developed interactive videos-based course of Code of Ethics, and subsequently their interest, engagement, and performance were evaluated. Descriptive and inferential statistics were used for analysis. It was found that the interactive videos help to enhance the level of interest and engagement among the participants, which leads to result in enhancing student performance due to knowledge retention.